An Experimental Analysis of a Frost-free Refrigerator using a Variable Capacity Compressor - Wang Wei; Wang Rui; Qin Zongmin (Zhileng xuebao)
A frost-free refrigerator with a variable capacity compressor(VCC) is studied based on the results from experiments and simulation. Analyses are conducted in terms of the system energy consumption, power and running percentage under several different compressor speeds. Moreover, the temperature variation in fresh food storage, freezer, fruit vegetable and the ice-making compartments is also discussed under different compressor running speeds respectively. The experimental results show that the temperature variation in all the compartments could be kept in a reasonable scope when the compressor is running at an optimal speed. The average temperature of the fresh food storage compartment is 4.1℃ with a maximum deviation of 3.4℃ and the average temperature in the fruit vegetable compartment is 6.1℃ with a max deviation of 1.0℃. With the help of VCC the energy consumption of this frost-free refrigerator can reach 0.908kWh/day when the temperatures in all the compartments reach the national standard requirement. What’s more, compared to the experimental result the simulated system energy consumption is higher by 16.2% when the compressor runs at 3000r/min, however it drops to 8.6% when the compressor speed is set at 1900r/min. The comparison results prove the reliability of the simulation software and also indicate the importance of further work on system model optimization .